2010
DOI: 10.1002/andp.201010420
|View full text |Cite
|
Sign up to set email alerts
|

Metric-affine f(R)-gravity with torsion: an overview

Abstract: Torsion and curvature could play a fundamental role in explaining cosmological dynamics. f (R)-gravity with torsion is an approach aimed to encompass in a comprehensive scheme all the Dark Side of the Universe (Dark Energy and Dark Matter). We discuss the field equations in empty space and in presence of perfect fluid matter taking into account the analogy with the metric-affine formalism. The result is that the extra curvature and torsion degrees of freedom can be dealt under the standard of an effective scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 23 publications
(39 reference statements)
1
70
0
Order By: Relevance
“…Equations (3.2a) are by construction symmetric. The symmetrization symbol for the Ricci tensor R ij is omitted because any connection satisfying equations (2.5), (2.6) and (3.2b) gives rise to a Ricci tensor that is automatically symmetric [1,3,4]. We also notice that, if f (R) = kR, we have non-vanishing torsion even if the spin density is zero.…”
Section: Geometrical Preliminariesmentioning
confidence: 99%
“…Equations (3.2a) are by construction symmetric. The symmetrization symbol for the Ricci tensor R ij is omitted because any connection satisfying equations (2.5), (2.6) and (3.2b) gives rise to a Ricci tensor that is automatically symmetric [1,3,4]. We also notice that, if f (R) = kR, we have non-vanishing torsion even if the spin density is zero.…”
Section: Geometrical Preliminariesmentioning
confidence: 99%
“…This is a direct consequence of the new field equations which can lead to the existence of additional radiative modes. Using a linearized approach, several studies investigated the additional polarization modes in all versions of f (R) theories ( [10][11][12][13][14][15], or more recently [16]) and scalar-tensor theories [17], and it has been shown that only one massive longitudinal mode exists along with the two usual tensorial modes of GR. In addition to the linearized approach, another powerful tool to study the properties of GWs in any metric theory is the Newman-Penrose (NP) approach developed by Eardley et al [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in [12,13], the Cartan torsion tensor plays the role of spin source in the gravitational field equations where the affine connection is not simply Levi-Civita. Furthermore, as demonstrated in [106,[117][118][119], torsion plays an important role in Extended Theories of Gravity since brings further gravitational degrees of freedom responsible of chiral interactions. In other words, torsion is not only the source of spin but, thanks to the non-trivial structure of connections Γ α βγ , can give rise to chiral interactions of geometric origin [120].…”
Section: Gl(4)mentioning
confidence: 99%